Experimental set-up for an IoT power supply with an 130 nm SC DC-DC converter - Madeira, Ricardo (2019)
This work was supported by the Portuguese Foundation for Science and Technology under a Ph.D. Grant (SFRH/BD/115543/2016), and by PROTEUS project funded by the European Union's H2020 Programme under grant agreement no 644852.